The influence of treatment on cold work tool steel SKD 11 with temperature variations on mechanical properties - Hasanah, Indah Uswatun; Priadi, Dedi; Dhaneswara, Donanta; Alhamidi, A. Ali (Jurnal Teknika, 2023)
SKD 11 steel is a type of cold work tool steel that is popular and widely used in the manufacturing industry. SKD 11 steel is generally applied as dies, molds, cutting tools or others. Because of these applications. SKD 11 steel must have good wear resistance, hardness, dimensional stability, and toughness. So to improve the characteristics of the steel, a heat treatment process is carried out, but due to the high carbon content and alloying elements in the tool steel, the martensite finish (Mf) temperature of the steel becomes lower, so after the heat treatment process, usually the steel still leaves a lot of austenite phase. or commonly known as residual austenite. Residual austenite can affect the mechanical properties of SKD 11 steel, residual austenite can be removed by carrying out a cryogenic treatment process, this process is carried out after the quenching process. The heat treatment process this time was carried out using a vacuum furnace using an austenite temperature of 1040℃ and quenching using a medium in the form of nitrogen gas with a pressure of 3 bar. The cryogenic treatment process that was carried out afterward was carried out by varying the temperature of -80℃, -110℃, and -140℃. The test results obtained were then analyzed using an optical microscope and XRD (X-ray diffraction), as well as hardness testing and impact testing to determine the mechanical properties of the steel. Based on the research results it is known that the resulting microstructure contains martensite matrix and carbide M7C3 as primary carbide and M23C6 as secondary carbide, then by carrying out the cryogenic treatment process can reduce the percent of residual austenite, the lowest percent of residual austenite is obtained from the results of the cryogenic treatment at -140℃, which is equal to 1.15%. This is directly proportional to the hardness test results obtained, where the highest hardness value was also obtained by the sample with a value of 61.5 HRC, while the relationship with toughness is inversely proportional. The higher the hardness, the lower the resulting toughness.